2020
DOI: 10.1177/0021955x20943110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure drop rate and CO2 content on the foaming behavior of newly developed high-melt-strength polypropylene in continuous extrusion

Abstract: We report systematic studies on the foamability of our novel high-melt-strength long-chain branched polypropylene under supercritical CO2. Continuous foaming experiments were conducted using a tandem extrusion system and a set of filamentary dies with similar pressure drops but different pressure drop rates. The foam expansion was controlled by varying the temperature at the die exit. Under identical CO2 loadings, the expansion ratio plotted as a function of die temperature exhibited similar shapes across mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Therefore, it can be concluded that foaming induced at temperatures at least 8 °C above T c,onset may lead to sensible expansion of the molten polymer–gas mixture. When the foaming temperature is further above T c,onset , optimal foaming behavior—characterized by high volume expansion and uniform cell density—is achieved, which often emerges as a “mountain-shaped” profile in continuous foaming processes as the die temperature approaches the crystallization temperature of the polymer–gas mixture [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that foaming induced at temperatures at least 8 °C above T c,onset may lead to sensible expansion of the molten polymer–gas mixture. When the foaming temperature is further above T c,onset , optimal foaming behavior—characterized by high volume expansion and uniform cell density—is achieved, which often emerges as a “mountain-shaped” profile in continuous foaming processes as the die temperature approaches the crystallization temperature of the polymer–gas mixture [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, differences in foaming behaviors amongst resins between UC and AV CBA can be attributed to increased gas yield in AV CBA. As noted earlier, higher amounts of dissolved gas allow for increased cell density and smaller cell sizes [ 14 ]. The higher amounts of dissolved CO 2 also lower T c of PP [ 13 , 25 ] which decreases sensitivity to packing time amongst the resins.…”
Section: Resultsmentioning
confidence: 89%
“…Evidence of suppressed cell nucleation is reflected in the decrease in cell density with increasing packing time in all resins ( Figure 5 a,b). Further, the higher cell density, smaller cell sizes, and decreased sensitivity to packing time at higher CBA wt% can be partly attributed to decreased T c of PP due to CO 2 plasticization [ 13 , 14 , 25 ], which is further evidence that foaming under these test conditions is dominated by crystallization. From these trends, it can be postulated that the injected melt subjected to a longer packing time has been excessively cooled to a point that a larger portion of the polymer has solidified and lost more of its capability to foam upon mold opening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, some studies have been conducted on PP foams manufactured by injection molding, [13][14][15][16] compression molding [17][18][19] and extrusion molding. 20,21 For example, Ahmadi and Hornsby reported how the structure of PP foams was influenced by the injection molding processing conditions. 13 The effect of injection speed, shot weight, mold temperature and melt temperature were investigated.…”
Section: Introductionmentioning
confidence: 99%